The recruitment process and recommendation on redesigning of the job portal of Robi Axiata Limited - Ali, Syeda Nabilah (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.